Enhancing Culinary Students’ Comprehension of English Recipe Texts through Project-Based Learning - Moh. Arifin; Lailatul Ladhifah (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigates the effectiveness of Project-Based Learning (PjBL) in enhancing reading comprehension of English culinary texts among tenth-grade vocational culinary students at SMK Miftahul Ulum Solokuro. Employing a one-group pretest-posttest design, 28 students participated in four project-based sessions focused on understanding and applying English recipe texts. The results showed a statistically significant improvement, with average scores increasing from 48.5 (pre-test) to 83.68 (post-test). The paired-sample t-test revealed a p-value of 0.000, and the effect size measured by Cohen’s d was 3.74, indicating a very large effect. These findings highlight PjBL’s effectiveness in bridging the gap between academic English reading and real-world culinary practices. By contextualizing learning through projects, students not only improved their reading comprehension but also acquired essential skills for workplace readiness in the culinary industry